Alces alces - Peter Grubb (Smithsonian Institution Press, 1993)
Alces alces (Linnaeus, 1758). Syst. Nat., 10th ed., 1:66. TYPE LOCALITY: Sweden. DISTRIBUTION: N Eurasia from Scandinavia and Poland, east to Anadyr region (E Siberia); south to Ukraine and S Siberia, N Mongolia and N China (Xingjiang, Inner Mongolia, Heilongjiang); Alaska (USA); Canada; N USA; extinct in Caucasus region since last century; introduced to New Zealand. SYNONYMS: americanus, andersoni, angusticephalus, antiquorum, bedfordiae, buturlini, cameloides, caucasicus, columbae, coronatus, europaeus, gigas, jubata, machlis, meridionalis, palmatus, pfizenmayeri, shirasi, tymensis, uralensis, yakutskensis. COMMENTS: Revised by R.L. Peterson (1952); reviewed by Franzmann (1981, Mammalian Species, 154). Published as part of Peter Grubb, 1993, Order Artiodactyla, pp. 377-414 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 389, DOI: 10.5281/zenodo.7359189